FRAMING ANTI-AMERICAN SENTIMENT AND ITS IMPACTS ON TWO MUSLIM COUNTRIES: A Preliminary Analysis - Jati, Wasisto Raharjo (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2021)
The term “anti-American” sounds debatable in analyzing the relationship between Islamic world and United States. This term arguably stems from Huntington’s thesis on clash of civilization, which argued that the culture is the main belligerent instead of countries in the conflict. Two main cultures: the contrast between the West and Islam often eventually shapes the rivalry relationship between these two civilizations. Investigating the persistence rivalry between the two through critical literature review method, this article tries to answer the question of why Muslims are still hostile to American culture. It further argues that that media, which are mostly from Middle Eastern countries, have essential in shaping the fluctuated trend of anti-American sentiment among Muslims. This heavily depends on the impact of US foreign policy on Arab that might precipitates anti-American sentiments.